Response of the Invasive Cyanobacterium Raphidiopsis raciborskii to Iron and Phosphorus Concentrations in the Habitat: Effects on Growth and Cellular Phosphorus Distribution - Wenting Shen; Han Yang; Gaibian Ding; Bo Li; Xin Gan; Zijie Yuan; Liqing Wang; Wei Zhang (Diversity)
Harmful Raphidiopsis raciborskii blooms threaten aquatic ecosystems via toxin production, hypoxia induction, and biodiversity loss. To elucidate the synergistic regulatory mechanisms of Fe3+ and phosphorus (P) in cyanobacterial growth, we used a sterile pure culture system under laboratory conditions. We set different phosphorus sources (organic phosphorus and inorganic phosphorus) and low phosphorus concentration of R. raciborskii culture medium for culture, and set different Fe3+ addition amount to determine the basic growth index of cyanobacteria cells and the phosphorus content of different components. The results revealed that under conditions of sufficient inorganic phosphorus, there was a logarithmic relationship between ferric ammonium citrate (Fe3+) and the specific growth rate of R. raciborskii. Fe3+ > 2 mg/L enhanced IPS enrichment and biomass accumulation. However, in oligotrophic or mesotrophic environments with low inorganic phosphorus concentrations, the effect of Fe3+ on the growth of R. raciborskii contrasted with that observed in high-IP (eutrophic) environments, exhibiting a pattern of ‘low promotion and high inhibition’. Under organic phosphorus conditions, R. raciborskii converted phosphorus by increasing alkaline phosphatase activity (APA), but this metabolic compensation failed to restore physiological functions, resulting in growth suppression and enhanced cellular phosphorus reserves. Our results establish quantitative linkages between Fe3+-P co-limitation thresholds and algal adaptive responses, providing mechanistic insights for controlling bloom dynamics through targeted manipulation of Fe-P bioavailability.